2016
DOI: 10.5056/jnm15167
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Dimensions of Bloating in Functional Gastrointestinal Disorders

Abstract: Background/AimsBloating is common bothersome symptoms and most studies conducted in the Western countries found that bloating was frequently associated with lower gastrointestinal (GI) symptoms but many patients complaint bloating as upper GI symptoms in the clinical setting. This study was conducted to assess the prevalence of bloating, and to identify symptom grouping and finally document the impact of bloating in the diagnosis of functional GI disorders. MethodsParticipants in a comprehensive health-screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 28 publications
(37 reference statements)
3
16
0
Order By: Relevance
“…Studies have shown that younger patients are more likely to experience bloating. 5 Our study builds upon this knowledge, and we found as age increased, severity of bloating decreased. Visceral hypersensitivity is one possible pathophysiologic mechanisms of bloating 12,13 and younger age has been positively associated with visceral hypersensitivity.…”
Section: Discussionsupporting
confidence: 60%
“…Studies have shown that younger patients are more likely to experience bloating. 5 Our study builds upon this knowledge, and we found as age increased, severity of bloating decreased. Visceral hypersensitivity is one possible pathophysiologic mechanisms of bloating 12,13 and younger age has been positively associated with visceral hypersensitivity.…”
Section: Discussionsupporting
confidence: 60%
“…We used symptoms to identify naturally occurring clusters in the data. We considered all intestinal symptoms that can be associated with IBS, such as upper and lower abdominal pain or discomfort, change in stool form or frequency, abdominal bloating, dyspepsia, gastro‐oesophageal reflux, and post‐prandial symptoms and nausea . We also considered individual items from the PHQ‐15 questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Bloating is one of the most frequent symptoms reported by patients with gastrointestinal functional disorders [ 1 , 2 , 3 , 4 ]. In particular, over 90% of subjects with irritable bowel syndrome (IBS) complain of bloating [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ] and, in addition, 20–30% of the general population suffers this functional gastrointestinal discomfort [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%